1973
DOI: 10.1111/j.1476-5381.1973.tb06906.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐Adrenoceptor blocking properties and cardioselectivity of M & B 17,803A

Abstract: Summary1. The ,8-adrenoceptor blocking properties of (± )-1-(2-acetyl-4-n-butyramidophenoxy)-2-hydroxy-3-isopropylaminopropane hydrochloride (M&B 17,803A) have been compared with those of practolol and propranolol in the guinea-pig. cat and dog. 2. Following either intravenous or oral administration in the cat or dog, M&B 17,803A and practolol had similar potency in antagonizing isoprenalineinduced tachycardia and both showed cardioselectivity, but both were less potent than propranolol. 3. M&B 17,803A and pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
43
1

Year Published

1974
1974
1986
1986

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 15 publications
7
43
1
Order By: Relevance
“…The observed cardio-selectivity of acebutolol was comparable with that of practolol as in other studies using anaesthetized dogs (Briant, Dollery, Fenyvesi & George, 1971;Basil et al, 1973) but Baird & Linnell (1972) found this drug to be much less cardioselective in guinea-pigs and there is doubt about its selectivity in man (see Basil et al, 1973;Briant, Dollery, Fenyvesi & George, 1973).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The observed cardio-selectivity of acebutolol was comparable with that of practolol as in other studies using anaesthetized dogs (Briant, Dollery, Fenyvesi & George, 1971;Basil et al, 1973) but Baird & Linnell (1972) found this drug to be much less cardioselective in guinea-pigs and there is doubt about its selectivity in man (see Basil et al, 1973;Briant, Dollery, Fenyvesi & George, 1973).…”
Section: Discussionmentioning
confidence: 48%
“…Some of these drugs, notably propranolol, frequently induce respiratory distress in asthmatic subjects, an effect thought to result from block of ,¢adrenoceptors in airways smooth muscle (McNeill, 1964;Richardson & Sterling, 1969 practolol . In clinical trials with asthmatic subjects practolol caused a much lower incidence of respiratory side effects than propranolol (MacDonald & McNeill, 1968;Bernecker & Roetscher, 1970 (Basil, Jordan, Loveless & Maxwell, 1973). The cardioselectivity of practolol and similar agents probably results from differences in the nature of the 3-adrenoceptors in cardiac and airways smooth muscle.…”
mentioning
confidence: 99%
“…The oral doses of propranolol and acebutolol required to halve the potency of intravenous isoprenaline in producing tachycardia were 0.15 and 0.9 mg/kg respectively at 40-80 min, confirming that with the conditions of this experiment the two compounds have ,B-adrenoceptor blocking potency comparable with that seen in other species (Basil et al, 1973b). …”
Section: Introductionsupporting
confidence: 66%
“…Propranolol was the most potent of the drugs tested in reducing the frequency of ectopic beats following methylchloroform and adrenaline administration in the anaesthetized cat and the order of potency (propranolol, acebutolol, prac-tolol) of the 3-adrenoreceptor blocking agents in this test follows their order of potency in inhibiting cardiac 3-receptors (Basil et al, 1973b). Furthermore the doses used, 0.01-2 mg/kg, are low compared to the doses required to revert an established ouabain-induced arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation